Perlindungan Hukum Atas Perbuatan Hukum Rekayasa Menganeksasi Tanah Sengketa - Zahra, Siti Athirah; Retnaningsih, Sonyendah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Land Registration is an intended activity to provide guarantees of legal certainty of land rights in the form of land rights certificates, but at the process to registrate of land there is some obstacle because there people who do not materially do annexation the land. The purpose of this study is to determine the legal protection for holders of Kohir which yet become certificate of land because of annexation of the land. The form of usurpation of land ownership rights. The approach method used is normative juridical. The result showed the act of annexation of land was an unlawful act against the law, contained in article 1365 code of Civil Law.